Evaluation and value addition of watery rose apple (syzygium (Burm) alston) and malay apple (syzygium malaccense )L) mernil and perry) - Anu Mary Markose (Department of Processing Technology, College of Horticulture, 2008)
Watery rose apple and Malay apple belong to the family of Myrtaceae. The fruits are rich in vitamin C and have many medicinal properties. A major chunk of production of this crop is being wasted due to the lack of scientific handling and processing technologies. In this context, the present investigation “Evaluation and value addition of watery rose apple and Malay apple” was taken up to standardize technologies for processing and value addition of these fruits. The fruits were primarily classified into different groups based on their colour. The physico chemical attributes in relation to colour was not apparent. Difference was significant in quality attributes with respect to size of fruits in Malay apple. Big fruits possessed most of the desirable attributes for product development. Among the three different types weight of fruits and titrable acidity differed significantly. Accessions within each type recorded significant variation in most of the quality attributes studied. Based on this suitability of accessions for preparation of different value added products were fixed. Osmoextraction was selected as the ideal method for production of quality pulp/juice. A simple method for preparation of beverages and jam using osmoextracted pulp/juice was developed. The pulp and juice extracted through this method exhibited good storability and served as the basic material directly for the preparation of different beverages. Osmodehydrated product prepared by dipping fruit slices of pink watery rose apple and Malay apple in 60 °Brix solution followed by vacuum drying at 50 °C for 48 hours was found acceptable. In white watery rose apple dipping the fruit slices in 70 °Brix was found superior. The osmodehydrated product exhibited a shelf life of two months without any microbial contamination in both glass and plastic containers. The pickle prepared using fresh fruit slices in all the three types of fruits acquired highest score. When heat treatment was adopted for preparation of fruits for pickling, the material became very soft and consistency of the product was lost. Wine prepared using fruit slices, sugar and water in the ratio of 1:1:0.5 scored the maximum value in organoleptic evaluation. Crushing the fruits was not good for production of quality wine as it caused loss of clarity. Pulp and juice based products viz., squash, RTS beverage and jam prepared using the osmoextracted pulp/juice in conformation with FPO standards were scored good by the judges. Products prepared using pink watery rose apple was found to be the best compared to other types as it possessed attractive pink colour. Method for extracting the natural colour anthocyanin present in Malay apple flowers was standardized. The best treatment identified for extracting anthocyanin from Malay apple flowers was incubation in citric acid 4 % for twelve hours. For the fruits of pink watery rose apple, incubation in citric acid 5 % for six hours yielded maximum anthocyanin. The quantity of anthocyanin extract required to colour the various products were standardized. The retention of colour in the products during storage was very less.